2015
DOI: 10.4209/aaqr.2014.09.0206
|View full text |Cite
|
Sign up to set email alerts
|

Small-Scale Study of Siberian Biomass Burning: I. Smoke Microstructure

Abstract: Reliable assessment of the impact of Siberian boreal forest wildfires on the environment and climate necessitates an improved understanding of microphysical and chemical properties of emitted aerosols. Smoldering, flaming and mixed fires of typical Siberian biomass (pine and debris) were simulated during a small-scale study in a Large Aerosol Chamber (LAC). Individual particle analysis of PM 10 and PM 2.5 smoke morphology and elemental composition revealed a strong dependence on combustion temperature, i.e., a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 51 publications
(79 reference statements)
6
38
1
4
Order By: Relevance
“…Several extensive studies have been conducted to characterize BB aerosols world-wide (e.g., Popovicheva et al, 2015;Lee et al, 2016 and references therein), including studies over the Indochina region: Myanmar, Thailand, Laos, Cambodia, and Vietnam (e.g., Lee et al, 2011;Chuang et al, 2013;Lee et al, 2016). Chuang et al (2013) characterized the aerosol chemical properties from near-source BB in northern Indochina during the Seven South East Asian Studies (7-SEAS)/Dongsha Experiment, and reported a significant contribution by the smoldering state of softwood burning.…”
Section: Introductionmentioning
confidence: 99%
“…Several extensive studies have been conducted to characterize BB aerosols world-wide (e.g., Popovicheva et al, 2015;Lee et al, 2016 and references therein), including studies over the Indochina region: Myanmar, Thailand, Laos, Cambodia, and Vietnam (e.g., Lee et al, 2011;Chuang et al, 2013;Lee et al, 2016). Chuang et al (2013) characterized the aerosol chemical properties from near-source BB in northern Indochina during the Seven South East Asian Studies (7-SEAS)/Dongsha Experiment, and reported a significant contribution by the smoldering state of softwood burning.…”
Section: Introductionmentioning
confidence: 99%
“…1.4), as was observed in smoke emissions from flaming burns of other biomass species (Popovicheva et al, 2014a). These particles probably contain OC with relative abundances in total carbon as high as 32% and 37% in pine and debris smoke, respectively (Popovicheva et al, 2015b).…”
Section: Fractionation With Respect To Morphology and Compositionmentioning
confidence: 61%
“…Sulfates may be condensed on soot particles forming internally mixed soot and do not change soot morphology, as shown in Popovicheva et al (2015b). They may also form irregular-shaped particles of salts ( Fig.…”
Section: Fractionation With Respect To Morphology and Compositionmentioning
confidence: 99%
See 2 more Smart Citations